Assessment of Antimicrobial and Antibiofilm Effect of Salvia officinalis Extract Against Multidrug Resistant Pathogenic Escherichia coli - Ali, Kadhum Attia (Iraqi Journal of Science, 2025)
Fifty-five Escherichia coli isolates were obtained from urinary tract infections using classical methods and the VITEK system. Antibiotic sensitivity testing revealed that 33 (60%) of the pathogenic E. coli isolates were classified as multidrug-resistant (MDR). The study found that the majority of the isolates revealed resistance to ampicillin and ceftazidime, and their resistance ratios were 94.54% and 72.72%, respectively. In contrast, the most effective antibiotics were ertapenem, imipenem and tigecycline, and their resistance ratios were 5.45%, 9.09% and 10.9%, respectively. The aim of the current study is to assess the antimicrobial and antibiofilm formation activity of Salvia officinalis extract against MDR pathogenic Escherichia coli. All 33 isolates of MDR pathogenic E. coli displayed biofilm formation ability extended from moderate to strong. Ethanol extract of Salvia officinalis plant leaves revealed antibacterial activity against all MDR E. coli isolates at the concentration of 100 mg/ml, 200 mg/ml, and higher than these concentrations. Additionally, Salvia officinalis extract also exhibited antibiofilm formation activity against all MDR pathogenic isolates at the concentration of 50 mg/ml.